Elastic behavior of stiffened curved plates subjected to transverse loading (2018)
This paper presents a numerical study on the elastic behavior of stiffened curved plates subjected to transverse loading. The analyses are performed by means of linear static analysis using finite element modelling. Firstly, flat plates under transverse loading (uniform and non-uniform-trapezoidal) are modelled to validate the computational model against analytical solutions available in the literature. Secondly, the behavior of unstiffened curves plates under transverse loading is analyzed. Then, the influence of both, transversal and longitudinal stiffening in controlling the out-of-plane displacements and stresses distribution of the curve plates is demonstrated. Finally, a case-study concerning the response of a hydroelectric power plant intake gates subjected to a hydrostatic head is further investigated. The results show that the increase in gate stiffness is reflected in smaller deformations implying a better performance and system integrity.